Analysis of the Influence of Mosque Service Quality and Mosque Building Anatomy on Mosque Congregation Satisfaction: Analisis Pengaruh Mosque Service Quality dan Anatomi Bangunan Masjid terhadap Kepuasan Jamaah Masjid - mulyandi, Rachman; Effendi, Andrey Caesar; Tio Fabian, Natanael; Parsius, Angel Andromeda (Academia Open, 2026)
General Background: Mosques function not only as worship spaces but also as social and spiritual institutions that require adequate service quality and supportive architectural design. Specific Background: This study examines congregants’ worship experiences through mosque service quality and mosque building anatomy, including physical facilities, reliability, responsiveness, assurance, empathy, structural design, aesthetics, spatial function, and environmental context. Knowledge Gap: Previous discussions on mosque satisfaction have often treated service quality and building anatomy separately, while limited qualitative evidence explains how both dimensions form congregants’ comfort, solemnity, and satisfaction. Aims: This study aims to describe congregants’ perceptions of mosque service quality and building anatomy in relation to satisfaction during worship activities. Results: In-depth interviews with five male congregants showed that clean ablution and toilet facilities, reliable audio systems, responsive mosque staff, empathy, accessibility, organized zoning, aesthetic design, functional prayer spaces, environmental calmness, waste management, greenery, and energy-saving lighting shaped positive worship experiences. The findings also identified practical concerns, including the need to expand ablution areas, maintain water quality, improve cooling facilities, and optimize natural lighting. Novelty: The study offers an integrated qualitative view of service and sacred architecture as interconnected dimensions of congregant satisfaction. Implications: Mosque managers and planners should align service management and architectural planning to strengthen comfort, solemnity, social interaction, and the mosque’s broader spiritual role. Highlights • Clean facilities, responsive staff, and empathy formed positive worship experiences.• Structural design, aesthetics, zoning, and accessibility supported comfort and solemnity.• Ablution space, cooling facilities, water quality, and lighting need further attention. Keywords Mosque Service Quality; Mosque Architecture; Congregant Satisfaction; Worship Experience; Sacred Space